Theoretical and applied mathematics in international business - Christiansen, Bryan, 1960-; Shuwaikh, Fatima, 1977- (Business Science Reference, an imprint of IGI Global, 2020)
"This book examines the role of applied and theoretical mathematics in various areas of international business. These include the trade of goods, services, technology, capital and/or knowledge"--